Influence of Electrolyte on the Electrochemical Reduction of Carbon Dioxide Using Boron‐Doped Diamond Electrodes. Issue 36 (27th September 2018) - Tomisaki, Mai; Natsui, Keisuke; Ikemiya, Norihito; Nakata, Kazuya; Einaga, Yasuaki
Abstract: Electrochemical reduction of CO2 to useful compounds have been actively investigated. The faradaic efficiency and selectivity for products of CO2 reduction depend on some factors, such as electrode materials and electrolytes. Recently, boron‐doped diamond (BDD) was found to be a promising electrode material for production of formic acid by CO2 reduction, but the influence of electrolytes has not been sufficiently elucidated. Here, we studied the impact of various cations and anions on CO2 reduction using BDD electrodes. The faradaic efficiency for producing formic acid became higher by using larger alkali metal cations, because these hydrated cations would keep the pH near the cathode suitable for CO2 reduction by their buffer effect. Moreover, formic acid was efficiently obtained by using specifically‐adsorbed anions such as halides and sulfate. Finally, we achieved the maximum faradaic efficiency for producing formic acid as high as 95% in RbBr aqueous solution. Abstract : Suitable electrolyte for producing formic acid on BDD: the electrochemical reduction of CO2 on boron‐doped diamond (BDD) is conducted with various electrolytes. Large alkali metal cations give high faradaic efficiency for producing formic acid due to the buffering effect by hydrated cations. On the other hand, ammonium ions give large production of hydrogen. In addition, formic acid is obtained efficiently by using specifically‐adsorbed anions.